Herding behavior in the Indonesian Stock Exchange: the roles and contributions of foreign investors during the period 2006 to 2011 - Setyawan, Ignatius Roni; Ishak Ramli (Penerbit Universiti Kebangsaan Malaysia, 2016)
Domestic investors in the Indonesian capital market (IDX) tend to be very dependent on the behavior of foreign investors. It is assumed that most of the domestic investors in the IDX are like this, caused by an axiom that the bargaining position of foreign investors is stronger than that of the domestic investors and those of other emerging markets. This study tries to investigate whether the herding behavior exists and whether the assumption that foreign investors have caused instability is true or just a myth during the period 2006-2011.There are three objectives of the study: 1) To prove whether the conduct of domestic investors’ herding behavior in the IDX exists, 2) To prove whether the trading of foreign investors causes the herding behavior and 3) To prove whether the interaction between foreign and domestic investors affect the stock volatility. Using the data from 2006 to 2011, it is found that herding behavior in the IDX exists; moreover, by using VAR analysis, it also indicates that the occurrence of herding behavior is caused by negative feedback trading from foreign investors. The volatility analysis using Parkinson and Garman-Klass methods found the stock volatilities in the IDX increased, caused by the interaction of foreign and domestic investors.